The Toll of Vascular Insufficiency: Implications for the Management of Peripheral Arterial Disease. (21st February 2016) - Xu, Jun; Sachdev, Ulka
Abstract : Peripheral artery disease (PAD) can result in limb loss within six months of diagnosis in a subset of patients who cannot undergo endovascular or surgical revascularization yet continues to maintain a marginal position in cardiovascular research. While a body of literature continues to grow describing the role of danger signaling and innate immunity in cardiac biology, the role of these pathways in the ischemic myopathy associated with PAD has not been extensively studied. The following report will review the current literature on the role of Toll-like receptor (TLR) signaling in cardiovascular biology as well as in nonischemic myopathy. While attenuation of TLR signaling has not been shown to be clinically useful in the treatment of infectious inflammation, it may show promise in the management of severe arterial insufficiency.